PENGARUH KECEPATAN DEKOMPOSISI PUPUK ORGANIK CAIR LIMBAH TAHU TERHADAP SERAPAN N DAN S TANAMAN JAGUNG PADA ALFISOL - Anindita Kusumaningtyas; Yulia Nuraini; S Syekhfani (Jurnal Tanah dan Sumberdaya Lahan, 2015)
Alfisol is a soil having problems related to low pH, organic C and nutrient availability. Application of organic fertilizer may increase nutrient availability and plant growth. The purposes of this study were to determine the effect of the decomposition rate of liquid organic fertilizer of tofu waste to N and S on the soil, and to determine the effect of the decomposition rate of liquid organic fertilizer of tofu waste on uptake N and S in maize. This study used a completely randomized design with nine treatments and three replications. The results showed significant effects of the application liquid organic fertilizer of tofu waste on the pH, C-organic, total N, plant height, and leaf number. Application of liquid organic fertilizer of tofu waste previously decomposed for two days (P2 treatment) showed the best results at the beginning and end of the analysis. The total N at the P2 treatment increased 50% compared to the control treatment in the beginning of soil analysis and 23.51% in the end of the soil analysis. Application of liquid organic fertilizer of tofu waste gave no significant effect on N and S uptake by maize. Application of liquid organic fertilizer of tofu waste previously decomposed for twelve days (P7 treatment) gave the best results with an increase in N uptake by 107.62% compared to the control treatment.